2016
DOI: 10.1016/j.icarus.2015.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Titan’s temporal evolution in stratospheric trace gases near the poles

Abstract: We analyze spectra acquired by the Cassini/Composite Infrared Spectrometer (CIRS) at high resolution from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
91
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(113 citation statements)
references
References 31 publications
21
91
1
Order By: Relevance
“…The new calibration provides a better sensitivity for line detection and the enhanced radiance in some of the parts of the FP3 spectrum allows for a more precise inference of the abundances and their variation with time for some of the weaker species. The difference in the results still remains within the 10%-15% range with respect to the abundances published in Coustenis et al (2016).…”
Section: Observations and Analysismentioning
confidence: 45%
See 4 more Smart Citations
“…The new calibration provides a better sensitivity for line detection and the enhanced radiance in some of the parts of the FP3 spectrum allows for a more precise inference of the abundances and their variation with time for some of the weaker species. The difference in the results still remains within the 10%-15% range with respect to the abundances published in Coustenis et al (2016).…”
Section: Observations and Analysismentioning
confidence: 45%
“…We have already published an analysis of spectra acquired by Cassini/CIRS at high resolution from 2010 onward, both in nadir and limb mode and at high and middle latitudes (Coustenis et al 2013(Coustenis et al , 2016. In our 2016 work, we showed that the hydrocarbons found at high concentrations and longer lifetimes did not show significant latitudinal variability in the past years and until mid-2013.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations